Blockade of IL-36 Receptor Signaling Does Not Prevent from TNF-Induced Arthritis - Derer, Anja; Groetsch, Bettina; Harre, Ulrike; Böhm, Christina; Towne, Jennifer; Schett, Georg; Frey, Silke; Hueber, Axel (PLoS ONE, 2014)
Interleukin (IL)-36? is a newly described member of the IL-1 cytokine family with a known inflammatory and pathogenic function in psoriasis. Recently, we could demonstrate that the receptor (IL-36R), its ligand IL-36? and its antagonist IL-36Ra are expressed in synovial tissue of arthritis patients. Furthermore, IL-36? induces MAP-kinase and NF?B signaling in human synovial fibroblasts with subsequent expression and secretion of pro-inflammatory cytokines.To understand the pathomechanism of IL-36 dependent inflammation, we investigated the biological impact of IL-36? signaling in the hTNFtg mouse. Also the impact on osteoclastogenesis by IL-36? was tested in murine and human osteoclast assays.Diseased mice showed an increased expression of IL-36R and IL-36? in inflamed knee joints compared to wildtype controls. However, preventively treating mice with an IL-36R blocking antibody led to no changes in clinical onset and pattern of disease. Furthermore, blockade of IL-36 signaling did not change histological signs of TNF-induced arthritis. Additionally, no alteration on bone homeostasis was observed in ex vivo murine and human osteoclast differentiation assays.Thus we conclude that IL-36? does not affect the development of inflammatory arthriti
EVALuna2:12991